The Role of Local Wisdom in Optimizing Marine Resources to Increase the Economic Income of the Ujong Pancu Aceh Besar Community - Agustina, Lisa; Fitriani, Fitriani; Fatianda, Septian; Afni, Nur; Hasanah, Ida; Irwan, Irwan (Journal of Social and Policy Issues, 2025)
Ujong Pancu is a coastal area with abundant marine resources and high fishery potential, as well as marine biodiversity that is a source of livelihood for the local community. The purpose of this study is to observe and analyze the role of local wisdom in maintaining sustainable nature conservation, which has a direct impact on the community's economic income. This study uses a qualitative research method with a descriptive analysis approach. Data sources were obtained from observations and interviews with the community in Ujong Pancu. The results of the study show that local wisdom plays an important role in the lives of the people of Ujong Pancu. They still strongly uphold local values in preserving nature. Forms of local wisdom include the khanduri laot tradition, panglima laot, and respect for Islamic sharia law. The application of local wisdom also impacts community economic growth through the utilization of marine resources, such as fish catches, shrimp farming, marine tourism, and small and medium-sized businesses based on processed marine products.